Bilateral total shoulder arthroplasty: A systematic review of clinical outcomes. (August 2021) - Smith, John-Rudolph H; Houck, Darby A; Hart, Jessica A; Bravman, Jonathan T; Frank, Rachel M; Vidal, Armando F; McCarty, Eric C
Background: The purpose of this study was to describe the clinical outcomes following bilateral total shoulder arthroplasty (TSA). Methods: A systematic search of the PubMed, Embase, and Cochrane Library databases following PRISMA guidelines was performed. English-language literature published from 2010 to 2018 analyzing bilateral TSA (anatomic and/or reverse) with a minimum one-year follow-up was reviewed by two independent reviewers. Study quality was evaluated with the Modified Coleman Methodology Score and the methodological index for non-randomized studies score. Results: Eleven studies (1 Level II, 3 Level III, 7 Level IV) with 292 patients were included. Two studies reported on bilateral anatomic TSA ( n  = 54), six reported on bilateral reverse TSA (RTSA; n  = 168), two reported on anatomic TSA with contralateral RTSA (TSA/RTSA; n  = 31), and one compared bilateral anatomic TSA ( n  = 26) and bilateral RTSA ( n  = 13). Among studies, mean revision rate ranged from 0% to 10.53% and mean complication rate ranged from 4.9% to 31.3%. At final follow-up, patients experienced significant overall improvements in range of motion and patient-reported outcome score measurements. However, bilateral anatomic TSA resulted in greater improvements in external rotation compared to bilateral RTSA. Overall patient satisfaction was 91.0%. Conclusion: The available data indicate that bilateral TSA allows for functional and pain improvements and result in high patient satisfaction. Level of evidence: IV.